1995
DOI: 10.1152/jappl.1995.78.6.2115
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain composition in young and old rat skeletal muscle: effects of endurance exercise

Abstract: The objective of this study was to determine the effects of age and exercise on the myosin heavy chain (MHC) composition of skeletal muscle. Young (3 mo) and old (22 mo) female specific pathogen-free barrier-reared Fischer 344 rats were randomly assigned to young untrained or young trained and old untrained or old trained groups, respectively. Young trained and old trained animals performed endurance exercise training on a motorized treadmill for 8 wk. Succinate dehydrogenase activity and MHC isoforms were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
6

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 0 publications
8
67
1
6
Order By: Relevance
“…Silver staining of MHC bands revealed a transition from fast MHC-IIb to MHC-IIa to slow MHC-I in 8-month-versus 22-month-old muscles. This altered pattern of MHC expression agrees in general with the molecular processes that occur during fast-to-slow transitions, such as adaptations following chronic low-frequency stimulation of fast muscles (Pette and Staron, 2001) or endurance exercise (Sullivan et al, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…Silver staining of MHC bands revealed a transition from fast MHC-IIb to MHC-IIa to slow MHC-I in 8-month-versus 22-month-old muscles. This altered pattern of MHC expression agrees in general with the molecular processes that occur during fast-to-slow transitions, such as adaptations following chronic low-frequency stimulation of fast muscles (Pette and Staron, 2001) or endurance exercise (Sullivan et al, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…It was also conceivable that the intensity or period of exercise in this experiment was not so strong as to cause notable change of skeletal muscle fiber types. Sullivan et al showed that exercise training, which was 18-20 m/min treadmill running (60 min) 5 d/wk for 8 wk, resulted in a decrease in the percentage of type IIb MyHC (untrained, 43.0%; trained, 29.9%) and an increase in the percentage of type IIa MyHC (untrained, 14.0%; trained, 17.5%) in plantaris muscle in rats (16). Therefore, it is necessary to examine high intensity or long term effects of exercise training in order to check the synergistic effect of beef extract and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Each dietary group was furthermore subdivided into aerobically exercised and nonexercised groups (total 4 groups); Control: nonexercised, nonsupplemented, BE: nonexercised, supplemented, CE: exercised, nonsupplemented, BE ϩ CE: exercised, supplemented. Exercised subjects engaged in compulsory exercise for 30 min every other day with a treadmill running tool having 5% grade and 15 m/min speed and this protocol was assumed as low intensity endurance exercise compared with previous reports ( 16 ). The body weight of each group at the beginning of the experiment (after pre-feeding) was adjusted to be as identical as possible [276.8 Ϯ 9.4 (SD) g in Control, 265.6 Ϯ 17.4 g in BE, 275.1 Ϯ 10.8 g in CE, 265.2 Ϯ 13.7 g in BE ϩ CE].…”
Section: Methodsmentioning
confidence: 99%
“…This is reflected in the composition and level of expression of MyHC isoforms within these muscle. Various factors such as development, innervation, increased and decreased neuromuscular activity, physical activity (overloading and unloading), hormones and ageing, have been shown to influence the phenotypic expression of skeletal muscle fibers (Sullivan et al, 1995;Schiaffino and Reggiani, 1996;Pette and Staron, 2000). Skeletal muscle plasticity has been studied extensively by myosin isoform transitions in different experimental animal models, i.e.…”
Section: Introductionmentioning
confidence: 99%